Chronique juridique - collaborateurs, Divers (Assurances)

(untitled) (HEC Montréal, 1981)
Is the payment of a premium to the broker always considered as a payment to the insurer? Can an alderman be covered by a policy issued in the name of the municipality? The judgment rendered in Reibl vs. Hughes and its consequences. These are the questions studied hereunder by Me Rémi Moreau and Me Denise Dussault.